2022
DOI: 10.1002/2211-5463.13454
|View full text |Cite
|
Sign up to set email alerts
|

The spike glycoprotein of highly pathogenic human coronaviruses: structural insights for understanding infection, evolution and inhibition

Abstract: Highly pathogenic human coronaviruses (CoV) including SARS‐CoV, MERS‐CoV and SARS‐CoV‐2 have emerged over the past two decades, resulting in infectious disease outbreaks that have greatly affected public health. The CoV surface spike (S) glycoprotein mediates receptor binding and membrane fusion for cell entry, playing critical roles in CoV infection and evolution. The S glycoprotein is also the major target molecule for prophylactic and therapeutic interventions, including neutralizing antibodies and vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 168 publications
0
10
0
Order By: Relevance
“…A multiple sequence alignment of the spike protein of each virus demonstrated that MERS-CoV showed 30.63% homology to SARS-CoV and SARS-CoV-2 displayed 76.19% homology to SARS-CoV [ 64 ]. Interestingly, the RBD SARS-CoV-2, SARS-CoVs, and MERS-CoV display a similar architecture, consisting of a β-sheet core with a twisted five-stranded antiparallel β sheet and an inserted loop that directly interact with the receptor [ 65 ]. However, SARS-CoV-2-S RBD is more structurally similar to MERS-CoV RBD than SARS-CoV RBD to MERS-CoV RBD [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…A multiple sequence alignment of the spike protein of each virus demonstrated that MERS-CoV showed 30.63% homology to SARS-CoV and SARS-CoV-2 displayed 76.19% homology to SARS-CoV [ 64 ]. Interestingly, the RBD SARS-CoV-2, SARS-CoVs, and MERS-CoV display a similar architecture, consisting of a β-sheet core with a twisted five-stranded antiparallel β sheet and an inserted loop that directly interact with the receptor [ 65 ]. However, SARS-CoV-2-S RBD is more structurally similar to MERS-CoV RBD than SARS-CoV RBD to MERS-CoV RBD [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our third special issue of the year placed the limelight firmly on one specific virus: SARS‐CoV‐2. Guest editor Alexander Wlodawer commissioned three Review articles focussing on the structures of different proteins of SARS‐CoV‐2: Robin Stanley and co‐authors discussed the structure and function of ribonucleases [ 10 ]; Franck Martin and colleagues focussed on viral and cellular translation during SARS‐CoV‐2 infection, as mediated by NSP1 [ 11 ]; and finally, Xinquan Wang, Jiwan Ge and co‐authors discussed the evolution of and therapeutic targeting of the spike glycoprotein [ 12 ].…”
Section: New Developments In 2022mentioning
confidence: 99%
“…Although new vaccines have been implemented, the pandemic goes on through the rapid evolution of different variants, and it dramatically impacts all aspects of everyone’s life. Although there are several coronaviruses (CoVs) which are relatively mild, there are, apart from SARS-CoV-2, other highly contagious β-coronaviruses which in the past have also produced pandemic outbreaks, including SARS-CoV-1 and Middle East respiratory syndrome coronavirus [ 2 ]. SARS-CoV-2 cell entry can occur in two different ways, fusion with either the plasma membrane or with the endosomal one [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several coronaviruses (CoVs) which are relatively mild, there are, apart from SARS-CoV-2, other highly contagious β-coronaviruses which in the past have also produced pandemic outbreaks, including SARS-CoV-1 and Middle East respiratory syndrome coronavirus [ 2 ]. SARS-CoV-2 cell entry can occur in two different ways, fusion with either the plasma membrane or with the endosomal one [ 2 , 3 , 4 , 5 ]. Membrane fusion, essential for viral entry into the host cell, has been and is one of the main targets for the development of novel antiviral therapies to combat COVID-19.…”
Section: Introductionmentioning
confidence: 99%